2003
DOI: 10.1002/humu.9136
|View full text |Cite
|
Sign up to set email alerts
|

A Novel mutation L619F in the cardiac Na channel SCN5A associated with long-QT syndrome (LQT3): a role for the I-II linker in inactivation gating

Abstract: Congenital long QT syndrome type 3 (LQT3) is caused by mutations in the gene SCN5A encoding the α-subunit of the cardiac Na + channel (Nav1.5). Functional studies of SCN5A mutations in the linker between domains III and IV, and more recently the C-terminus, have been shown to alter inactivation gating. Here we report a novel LQT3 mutation, L619F (LF), located in the domain I-II linker. In an infant with prolonged QTc intervals, mutational analysis identified a heterozygous missense mutation (L619F) in the doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Until now 3 genes have been associated with 2:1 AV block: SCN5A, KCNH2, and CACNA1. 17,[27][28][29][30][31][32][33][34][35][36][37][38] Our data suggest that perturbations in the SCN4B-encoded ␤4 subunit constitute another pathogenic mechanism for 2:1 AV block in patients with LQTS.…”
Section: Discussionmentioning
confidence: 67%
“…Until now 3 genes have been associated with 2:1 AV block: SCN5A, KCNH2, and CACNA1. 17,[27][28][29][30][31][32][33][34][35][36][37][38] Our data suggest that perturbations in the SCN4B-encoded ␤4 subunit constitute another pathogenic mechanism for 2:1 AV block in patients with LQTS.…”
Section: Discussionmentioning
confidence: 67%
“…Five of the 10 have been functionally characterized previously, with L619F,21 P1332L,22 R1623Q,23 and E1784K24 producing channel abnormalities consistent with an LQT3 phenotype and G615E25 producing a wild-type-like SCN5A channel 10…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that previous studies demonstrated that LQT3 mutations located in the cytoplasmic linker between domains I and II (A572D, A572F, delAL586–587, G615E, L619F, and R680H) can either increase the persistent Na + current or shorten recovery times from inactivation 10,23,24. This suggests that the domain I–II linker, in addition to the domain III–IV linker and the C-terminus region25,26–29, might also be involved in stabilizing the channels’ fast inactivation.…”
Section: Discussionmentioning
confidence: 99%